2016
DOI: 10.1016/j.jsxm.2015.11.008
|View full text |Cite|
|
Sign up to set email alerts
|

Low-energy Shock Wave Therapy Ameliorates Erectile Dysfunction in a Pelvic Neurovascular Injuries Rat Model

Abstract: Introduction Erectile dysfunction (ED) caused by pelvic injuries is a common complication of civil and battlefield trauma with multiple neurovascular factors involved, and no effective therapeutic approach is available. Aims To test the effect and mechanisms of low-energy shock wave (LESW) therapy in a rat ED model induced by pelvic neurovascular injuries. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
97
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 56 publications
(21 reference statements)
3
97
0
2
Order By: Relevance
“…Our results showed that the nNOS content in both the MPG and the dorsal penile nerve was reduced in the CN traction group, which is consistent with results in other CN injury models [9,24,25]. The number of neurofilament-positive nerve fibers in the dorsal penile nerve also declined, indicating that the axon contents were decreased after CN traction, which is also consistent with previous studies [26,27]. These findings suggest that CN traction could impair erectile function by reducing both the total number of nerve fibers and the number of nNOS-positive nerve fibers in the dorsal penile nerve.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the nNOS content in both the MPG and the dorsal penile nerve was reduced in the CN traction group, which is consistent with results in other CN injury models [9,24,25]. The number of neurofilament-positive nerve fibers in the dorsal penile nerve also declined, indicating that the axon contents were decreased after CN traction, which is also consistent with previous studies [26,27]. These findings suggest that CN traction could impair erectile function by reducing both the total number of nerve fibers and the number of nNOS-positive nerve fibers in the dorsal penile nerve.…”
Section: Discussionsupporting
confidence: 92%
“…Несмотря на то, что диабетическая и после-операционная ЭД известны среди специалистов как заболевания, трудно поддающиеся терапии и у ряда таких пациентов УВТ в нашем исследовании не изменила эректильную функцию, оказалось, что средние значения индексов МИЭФ и SHIM в обеих подгруппах сразу после завершения курса УВТ повысились. Наши результаты могут служить клиническим подтверждением целесообразности применения УВТ при этих патологических состо-яниях, возможности которой ранее были успешно проверены на экспериментальных моделях крыс с сахарным диабетом [8,16] и повреждениями со-судисто-нервных пучков таза [17].…”
Section: Discussionunclassified
“…In this study (24), Tom Lue and his colleagues investigated the effects of two different treatment regimen using Li-ESWT (low energy: 0.06 mJ/mm 2 , 300 pulses, 3 Hz during 4 weeks and 1 week wash-out or high energy: 0.09 mJ/mm 2 , 1,000 pulses, 3 Hz during 4 weeks and 1 week wash-out) in a new experimental model of neurovascular ED produced by both bilateral cavernous nerve injury (CNI) and internal pudendal bundle (IPB) injury. This model is meant to mimic trauma-related ED that “ commonly occurs in the setting of pelvic surgery or as a result of local injuries such as improvised explosive device in battlefield […] ”.…”
mentioning
confidence: 80%
“…As such, these data are a very valuable contribution in the understanding of the mechanistic actions of Li-ESWT in an experimental setting of ED. Thus, Li and co-workers (24) should be both congratulated for this work and encouraged to pursue this line of much-needed basic science research.…”
mentioning
confidence: 99%